Biomechanical Comparison of Anatomic Single- and Double-Bundle Anterior Cruciate Ligament Reconstructions: An In Vitro Study. (July 2013) - Goldsmith, Mary T.; Jansson, Kyle S.; Smith, Sean D.; Engebretsen, Lars; LaPrade, Robert F.; Wijdicks, Coen A.
Background: Arthroscopic identification of the anteromedial (AM) and posterolateral (PL) bundle locations of the anterior cruciate ligament (ACL) has facilitated an improved quantitative description of ACL anatomy. Few studies have directly compared the biomechanical laxity of anatomic single-bundle (SB) versus anatomic double-bundle (DB) ACL reconstruction techniques based on precise anatomic descriptions. Hypothesis: Anatomic tunnel positioning for SB and DB reconstructions would produce comparable anterior-posterior and rotatory knee laxity. Study Design: Controlled laboratory study. Methods: Nine matched pairs of cadaveric knees were evaluated for the kinematics of intact, ACL-deficient, and either anatomic SB or anatomic DB ACL-reconstructed knees. Reconstruction tunnels were placed either centrally in the ACL footprint or within the AM and PL footprints. A 6 degrees of freedom robotic system was used to assess knee laxity with an 88-N anterior tibial load and a simulated pivot-shift test of combined 10-N·m valgus and 5-N·m internal tibial torques. Rotational motion was measured with internal and external torques of 5 N·m along with varus and valgus torques of 10 N·m. One-sample and 2-sample independent t tests were used to compare between groups ( P < .05). Results: No significant differences were found between anatomic SB and DB reconstruction groups during anterior tibial loading. Anterior tibial translations during simulated pivot shift had no significant differences between anatomic reconstruction groups. Tibial rotation for internal/external and varus/valgus torques showed no significant differences between anatomic reconstructions, with the exception of small (<3°) but statistically significant differences in internal rotation at 20° and 30° of flexion. Despite the similar behavior between the 2 anatomic reconstruction groups, neither technique was able to reproduce the intact state during an anterior tibial load. Conclusion: No significant differences in anterior translation were found between the anatomic SB and anatomic DB ACL reconstructions for simulated pivot shift or anterior tibial loading. Clinical Relevance: Although significant differences between reconstructions were observed for internal rotation, the small magnitude of these differences (<3°) may not have clinical significance.